A MCDA-based approach for facility location: an assessment of EV charging station placement - Chumbi Quito, Wilson Enrique [UNESP] (2024)
The number of electric vehicles (EVs) is rising in the automobile market, driven by public policies aimed at the global decarbonization of the transportation sector. The primary challenge with the growing EV presence is related to recharging issues. Careful location of public EV charging stations is crucial to maximize EV usage and address range anxiety among users. As the electricity demand for EV charging represents new load behavior, it is essential to assess the impact of charging station locations on long-term electrical grid planning. The selection of the most suitable site involves conflicting criteria, requiring the application of multi-criteria analysis. This study applies a geographic information system-based Multicriteria Decision Analysis (MCDA) approach to address charging station site selection, incorporating demographic criteria and energy density to model EV growth. Several methods, including Fuzzy TOPSIS, are applied to validate the selection of suitable sites. In this evaluation, a high EV penetration scenario is used to assess the impact of increased EV charging stations on substation capacity planning. The proposed method is applied in Cuenca, Ecuador. Results show the effectiveness of MCDA in assessing the impact of charging stations on power distribution systems, ensuring proper system operation within substation capacity limits.